2008
DOI: 10.1136/jech.2007.060772
|View full text |Cite
|
Sign up to set email alerts
|

Job loss from poor health, smoking and obesity: a national prospective survey in France

Abstract: Background and objectives:Health selection into unemployment may be either direct or operate by reference to health-related behaviours rather than health per se (indirect selection). Panel data are desirable to investigate selection effects, and the two types of selection processes may be concurrent. We examine jointly the roles of health and health-related behaviours as precursors of unemployment, in order to disentangle direct from indirect selection processes.Design:The data of a multi-round nationally repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 33 publications
8
88
2
2
Order By: Relevance
“…In the current study, smoking status was related to the risk of ERdHP in men, but not in women (Tables 3 and 4). This gender difference has been reported in previous studies showing that smoking increases the risk of early retirement in men, but not in women 14) . In the current study, obesity was linked to the risk of ERdHP in women, but not in men.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the current study, smoking status was related to the risk of ERdHP in men, but not in women (Tables 3 and 4). This gender difference has been reported in previous studies showing that smoking increases the risk of early retirement in men, but not in women 14) . In the current study, obesity was linked to the risk of ERdHP in women, but not in men.…”
Section: Discussionmentioning
confidence: 61%
“…However, other longitudinal studies have not shown significant associations between smoking and risk of early retirement 12) or disability pension 5) . Another study revealed that the impact of smoking on early retirement varies by gender; smoking increases the risk of early retirement in men, but not in women 14) . Further, some studies report that obese workers who have a body mass index (BMI) of 25 or more at age 25 have an increased risk of early retirement 12) ; this effect was not examined across gender, however.…”
mentioning
confidence: 99%
“…Firstly, there is health selection into non-employment (Jusot, Khlat et al 2008), and this may be especially so for lone mothers. Secondly, the health impact of not having an income from gainful employment may be especially damaging for lone mothers.…”
Section: Why Increased Risk Of Poor Health Among the Non-employed Lonmentioning
confidence: 99%
“…Studies have shown that there may be health selection into non-employment (Jusot, Khlat et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Pour analyser les relations complexes entre le chômage et l'état de santé [21], il est utile de distinguer trois types d'études : celles principalement évoquées ici, qui suggèrent que les problèmes de santé sont une conséquence directe ou indirecte du chômage et que ce lien causal dépend de facteurs de risque spécifiques [22][23][24] ; celles montrant qu'il existe également un lien causal inverse, à savoir qu'une mauvaise santé augmente le risque de devenir chômeur [25][26][27] ; enfin, celles rappelant que les problèmes de santé sont aussi le résultat d'un environnement social et/ou d'un mode de vie délétères qui favorisent en même temps la survenue de périodes d'accès aux soins, seront quelque peu atténués [40]. D'où l'importance de réaliser des études pour estimer plus précisément l'étendue du problème de santé publique représenté par le chômage dans la population française.…”
Section: Un Problème Complexeunclassified